If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 23 = 16x + -71 Reorder the terms: 23 + 6x = 16x + -71 Reorder the terms: 23 + 6x = -71 + 16x Solving 23 + 6x = -71 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 23 + 6x + -16x = -71 + 16x + -16x Combine like terms: 6x + -16x = -10x 23 + -10x = -71 + 16x + -16x Combine like terms: 16x + -16x = 0 23 + -10x = -71 + 0 23 + -10x = -71 Add '-23' to each side of the equation. 23 + -23 + -10x = -71 + -23 Combine like terms: 23 + -23 = 0 0 + -10x = -71 + -23 -10x = -71 + -23 Combine like terms: -71 + -23 = -94 -10x = -94 Divide each side by '-10'. x = 9.4 Simplifying x = 9.4
| (x^2)=1.8(0.3-x) | | 6-15(x+2)+12x=6x-(3x-4)+20 | | 2(3x-2)=4(x+2) | | 45+0.12x=49.32 | | (B+2)(-B^2+4b-3)= | | 8-6(x+4)+4x=4x-(2x-5)+11 | | 4x(3x+2)-3x(4x-5)=3x-8 | | (2z+9)(z-7)= | | (-x^4)+(8x^2)-2=0 | | (4w-4)(5w+6)= | | 7x=12x+10 | | X+8+x-6=3(x-5) | | 13d-5=60 | | -8p-8=56 | | (-2a-9)+(9+4)= | | x^2+y^2-8x+9y=-11.25 | | (4x+7)+(x-3)= | | 6x-39=4x-11 | | 3x^2+5x-2= | | 11=6x+5 | | 5x^2+20x-160= | | (X-6)+(2x+9)= | | 3c^2+14c+8=0 | | 3x^2-7x+2= | | 57-4x=5x+16 | | 6-5p=0 | | -6z+z=-4z-9-6z | | 80=(x+2)(x) | | (57.12-32)0.56=F | | 7x+2=20+2x | | 215=16x^2+32x | | (143-32)0.56=C |